STABILIZING THE ECOLOGICAL SITUATION IN THE ARAL SEA REGION, MITIGATING THE NEGATIVE IMPACT OF ENVIRONMENTAL PROBLEMS CAUSED BY DRYING UP THE ARAL SEA - Xolmurodova Sevinch Jumanazarovna; Mallayev Normamat Ramazonovich (Bright Mind Publishing, 2025)
This article describes the ecological problems of the Aral Sea region and the history of the Aral Sea drainage, its causes and the problems that arose as a result of its negative consequences and solutions to mitigate their impact. Statistical information and other data on water distribution are provided.
Keywords: Aral Sea, Amu Darya, Syrdarya, UN, Aral Sea, Red Book.